2009
DOI: 10.1097/jcp.0b013e31819a8d96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Escitalopram on Anxiety and Respiratory Responses to Carbon Dioxide Inhalation in Subjects at High Risk for Panic Disorder

Abstract: Escitalopram did not produce greater changes than placebo in panic responses or in ventilatory abnormalities seen during CO2 exposure. Future studies concerning the effects of antidepressants on responses to CO2 challenge should use a placebo-controlled design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Investigations in small groups of patients with panic disorder found that treatment with different SSRIs and SNRIs reduced subjective anxiety following 5 and 7% CO 2 challenge, when compared with baseline, pre-treatment inhalation (Gorman et al 2004). However, a larger study involving 3 min of 5% CO 2 in individuals “at high risk of panic disorder” found that 2-week administration of the SSRI escitalopram had no effect on self-report or autonomic indicators of anxiety (Coryell & Rickels 2009). Given that SSRIs typically take 2–4 weeks to exert notable therapeutic effects in GAD, longer drug administration may be needed to generate valid results.…”
Section: Neurochemistrymentioning
confidence: 99%
“…Investigations in small groups of patients with panic disorder found that treatment with different SSRIs and SNRIs reduced subjective anxiety following 5 and 7% CO 2 challenge, when compared with baseline, pre-treatment inhalation (Gorman et al 2004). However, a larger study involving 3 min of 5% CO 2 in individuals “at high risk of panic disorder” found that 2-week administration of the SSRI escitalopram had no effect on self-report or autonomic indicators of anxiety (Coryell & Rickels 2009). Given that SSRIs typically take 2–4 weeks to exert notable therapeutic effects in GAD, longer drug administration may be needed to generate valid results.…”
Section: Neurochemistrymentioning
confidence: 99%
“…The use of 5-HT 2/3 R antagonist significantly reduces the apnoea index in sleep apnoea patients but also reveals sedation and weight-gain as unwarranted side effects (Carley et al, 2007). A recent placebo controlled clinical trial completely failed to show effective treatment of respiratory abnormality in panic disorder (Coryell and Rickels, 2009). …”
Section: Therapeutic Use Of Serotonergic Drugs In Central Respiratmentioning
confidence: 99%
“…The only exception for positive results with SSRI was reported in the experiment conducted by Coryell et al, 65 in which 32 subjects responsive to hypercapnia undertook both a 35% CO 2 and a 5% CO 2 challenge test, followed by randomized allocation to receive a 2-week course of either 10 mg/d of escitalopram or placebo. At the end of the treatment/placebo period, tests were repeated, and the team concluded that escitalopram did not produce greater changes than placebo in panic responses or in ventilatory abnormalities seen during CO 2 exposure.…”
Section: Tricyclic Antidepressants and Ssrismentioning
confidence: 96%